Differences in Stereoscopic Luster Evoked by Static and Dynamic Stimuli. (May 2019) - Wendt, Gunnar; Faul, Franz
We compared the classic static stereoscopic luster phenomenon with a recently described dynamic variant ("counter modulation") to investigate whether they are related to the same or different processes. In the experiments, we presented pairs of center-surround stimuli haploscopically and measured the effect of the contrast between center colors on perceived luster. The center colors were either static or temporally modulated. In addition, we examined five color conditions (one achromatic, two equiluminant, and two mixed conditions) and three background conditions that influence the channel-wise polarities of the contrast of the two centers to the common surround. The results for static and dynamic stimuli differed in several ways, suggesting that they depend on different mechanisms: Compared with the static version, in dynamic stimuli, luster was perceived at markedly lower contrasts, did not depend on the sign of the contrast polarities, and appeared more steady. However, both phenomena seem also similar in some respects: In both cases, equiluminant stimuli led to lustrous impressions that were considerably less strong than those evoked by stimuli containing luminance variation, and the strength of the perceived luster was generally boosted with reversed contrast polarities.